Analysis of Price, Product Quality, and Promotion on Consumer Purchasing Decisions at Supermarket X Nganjuk - Al Hafidz, M. Rizqi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: This study aims to analyze the influence of price, product quality, and promotion on purchasing decisions at Supermarket X Nganjuk. Design/Method/Approach: The method used in this research is quantitative.Sampling technique using technique nonprobability sampling. The sample taken in this study were consumers who purchased products at Supermarket X Nganjuk totaling 40 people. This study used multiple linear regression analysis techniques and hypothesis testing (t-test and F-test). Research Findings: The results of the t-test study indicate that the variables of price, product quality, and promotion partially have a significant effect on purchasing decisions. Based on the results of the F test, it is known that the variables of price, product quality, and promotion simultaneously have a significant effect on purchasing decisions. Theoretical contribution/Originality: Price, product quality, and promotion factors are part of the marketing mix elements. This study can provide empirical data on how the combination of these elements influences consumer decisions in the local retail sector so that it can develop the concept of the marketing mix. Practitionel/Policy implications: This research provides insights that can be applied to optimize pricing strategies, improve product quality, and design more effective promotions and helps businesses understand local consumer behavior so they can adapt marketing strategies to their needs andpreferencecustomer. Research limitations: Because in this study it was proven that there are still other variables such as location, facilities,store atmosphere, and others that influence purchasing decisions, this can be used as material for conducting similar further research to obtain better results. Keywords: price, product quality, promotion and purchasing decisions